2020
DOI: 10.3389/fonc.2020.00249
|View full text |Cite
|
Sign up to set email alerts
|

B Cells as Prognostic Biomarker After Surgery for Colorectal Liver Metastases

Abstract: Background: The aim of this study was to identify more accurate variables to improve prognostication of individual patients with colorectal liver metastases (CRLM). Clinicopathological characteristics only partly explain the large range in survival rates. Methods: MessengerRNA expression profiles of resected CRLM of two patient groups were analysed by mRNA sequencing: poor survivors (death from recurrent disease <30 months after surgery) and good survivors (no recurrent disease >60 months after surgery). Tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In addition, other studies have shown that lymphoid follicle formation and plasma cell infiltration significantly associate with better prognosis after resection of LM-CRC, while macrophage does not. 22,97,98,100,101 These results collectively indicate that antitumor immunity, characterized by co-infiltration of T and B cells together with lymphoid follicle formation, is actively working to suppress tumor growth at least in some early/resectable LM-CRCs. It is still unclear and interesting to see whether increased lymphocytic infiltration can still be observed in cases of overt and unresectable metastases.…”
Section: Immune Microenvironment Of Liver Metastasis Of Colorectal Admentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, other studies have shown that lymphoid follicle formation and plasma cell infiltration significantly associate with better prognosis after resection of LM-CRC, while macrophage does not. 22,97,98,100,101 These results collectively indicate that antitumor immunity, characterized by co-infiltration of T and B cells together with lymphoid follicle formation, is actively working to suppress tumor growth at least in some early/resectable LM-CRCs. It is still unclear and interesting to see whether increased lymphocytic infiltration can still be observed in cases of overt and unresectable metastases.…”
Section: Immune Microenvironment Of Liver Metastasis Of Colorectal Admentioning
confidence: 81%
“…In LM-CRC, infiltration of T cells, B cells and macrophages are preferentially observed at the tumor margin compared with inside the tumor, 96 and increased lymphocytic infiltration is occasionally associated with lymphoid follicle formation 97 and plasma cell infiltration. 98 The CD117 + mast cell is a relatively rare population in LM-CRC but seems to be associated with intratumor fibrosis developing after neoadjuvant chemotherapy. 96 A detailed study of >600 synchronous and metachronous LM-CRCs by Galon's group has revealed that the amount of T-and B-cell infiltration varies among different synchronous and metachronous LM-CRCs from the same patient, 22 and these differences partly reflect different genetic evolutionary patterns among these metastatic lesions.…”
Section: Immune Microenvironment Of Liver Metastasis Of Colorectal Admentioning
confidence: 99%
“…27 According to a recent investigation, the heightened presence of CD79A+ B cells within the stromal environment is a favorable predictive factor for individuals undergoing surgery due to colorectal liver metastasis. 28 Nevertheless, the precise regulatory mechanism of CD79A in LUAD remains uncertain. IL11 belongs to the glycoprotein (GP) 130 cytokine family, which also has IL6 and IL27.…”
Section: Discussionmentioning
confidence: 99%
“…The PI model was then constructed by multivariate Cox CD79a is part of the B cell receptor, and most T cell neoplasms do not express CD79a proteins [20]. High immune infiltration of CD79a+ B cells in the tumor stroma tends to be associated with good survival in colorectal liver metastasis patients [21]. However, little is known regarding the underlying regulatory mechanism of CD79a in OS growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%